Indoor air pollutants level and its association with lung function amongst toll plaza workers / Basyirah Omar Mokhtar - Omar Mokhtar, Basyirah (2014)
Background: A cross- sectional study was done to assess indoor air pollutants level and lung function performance of the toll plaza workers based on their working shift as consequences of exposure to traffic pollution. Toll Plaza Batu 3, Shah Alam was selected as the study location. In order to associate the exposure and effects only manual toll collection lane workers were chosen as study respondents. Methodology: Indoor Air pollutants concentration of Particulate matter, (PM10), Nitrogen Dioxide( NO₂) and Sulfur Dioxide( SO₂) were determined by using EVM7 (Quest). The level of these air pollutants were measured in accordance to Time weighted Average of 8 hours each based on 3 different shifts A, Band C , total of sixty (n=60) toll plaza workers in the manual toll collection lane are chosen as the sampler for air quality and health questionnaire. Out of the sixty respondents only forty five (n=45) of them were selected to perform lung function test based on the inclusive criteria. The association between pollutants level, demographic data, health status and lung function test were analysed by using SPSS version 17.0. Results: The level of PM10, NO₂ and SO₂ complies with Schedule 1 Permissible Exposure Limit (USECHH), which the concentrations were different based on the work shift. Traffic Assessment shows there is no significant correlation of p>0.05, between the pollutants level (PM10, NO₂ and SO₂) with the number of vehicles, Moreover, there is a significant correlation between the highest sum of vehicles at shift B with the lung function test (FVC%). %).Furthermore, the significant association between the lung function test with the health symptoms, which all of the symptoms mentioned were positively correlated (p-value less than 0.01%) FEV1/FVC% with coughing symptoms, FVC% with wheezing symptoms and FEV1 /FVC % with runny nose symptoms. Besides, it is found that the lung function performance were inversely proportional with the working years. Conclusion: This study was conducted to quantify the concentration of air pollutants level (PM10,NO₂,SO₂), even though the results were still below the permissible exposure limit but there is some significant association in lung function performance and air quality and health related symptoms from a long term exposures of vehicles pollutants.